2023
DOI: 10.1038/s41598-023-38868-2
|View full text |Cite
|
Sign up to set email alerts
|

Speech emotion classification using attention based network and regularized feature selection

Abstract: Speech emotion classification (SEC) has gained the utmost height and occupied a conspicuous position within the research community in recent times. Its vital role in Human–Computer Interaction (HCI) and affective computing cannot be overemphasized. Many primitive algorithmic solutions and deep neural network (DNN) models have been proposed for efficient recognition of emotion from speech however, the suitability of these methods to accurately classify emotion from speech with multi-lingual background and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Existing studies support these findings. For instance, Samson et al [ 53 ] demonstrated that selecting representative features significantly improves classification accuracy in speech emotion recognition. Similarly, Saisanthiya et al[ 54 ]and Raheel et al [ 55 ] showcased the performance enhancement achieved by integrating heterogeneous features such as text or physiological signals in sound recognition tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies support these findings. For instance, Samson et al [ 53 ] demonstrated that selecting representative features significantly improves classification accuracy in speech emotion recognition. Similarly, Saisanthiya et al[ 54 ]and Raheel et al [ 55 ] showcased the performance enhancement achieved by integrating heterogeneous features such as text or physiological signals in sound recognition tasks.…”
Section: Discussionmentioning
confidence: 99%
“…KNN can perform regression and classification processes and K represents the number of nearest neighbors. KNN focuses on finding the smallest distance between neighbors, so it predicts the target based on the Euclidean distance (6). Figure 8 depicts the KNN classifier.…”
Section: ) K-nearest Neighbor (Knn)mentioning
confidence: 99%
“…Computers use data to enhance their algorithm and better process other data in the future [2]. Researchers are looking for techniques to extract the emotional state of a speaker from their words and to successfully understand human emotions [6]. Emotions may be represented in speech and then exploited to extract useful connotations from spoken words, therefore improving speech recognition implementations [4,7].…”
Section: Introductionmentioning
confidence: 99%